Molecular Identification of Thermally-tolerant Symbiotic Dinoflagellates from Hard Coral (Scleractinia) in Biawak Island, Indonesia (Microbiology Indonesia, 2017)
Symbiodinium is phototrophic dinoflagellates that occur as endosymbionts in various marine invertebrates and protists, forming mutualistic symbiosis with their hosts. The composition of Symbiodinium populations may also play an important role in the tolerance or sensivity of corals towards bleaching. Therefore, this research aims to identify thermally-tolerant Symbiodinium of scleractinian corals in Biawak Island using molecular techniques. Sampling was carried out from Acropora sp and Porites sp, from the depth of 3-5 meters. Symbiodinium was TMisolated through metagenomic approach using ZR Soil Microbe DNA Kit and 28S nrDNA gene was amplified TMusing Polymerase Chain Reaction (PCR). The resulted sequences were processed using BioEdit software and TMMEGA 5.2 for phylogenetic tree construction. The results indicated that isolates of ZX-ACP-ST.1 and ZXPORITES-ST.3 have similiarity to registered sequences of Symbiodinium thermophilum with identity value of TM99% and 98%. BLAST analysis of ZX-PORITES-ST.2 isolate indicated high identity (99%) to sequences of Symbiodinium sp. clade C while ZX-PORITES-ST.3 isolate has 99% similiarity to Symbiodinium sp. CG8. Phylogenetic analysis using UGPMA method showed that all isolates had a very close relationship and thought to have come from Symbiodinium clade C.